P Pendidikan Kesehatan Berbasis Health Belief Models Tentang Tanda Gejala Awal Stroke (Fast): Literatur Riview - Any Zahrotul Widniah (Journal of Nursing Invention, 2022)
Introduction:Stroke is a important health problem in the world, each year 5.5 million people die from stroke, and 44 million people lost their lives and were disabled. The stroke attack has a golden period, that is, if a stroke patient is treated immediately, disability and death can be avoided. The golden period of stroke is within the first 4 hours after the patient experiences the symptoms of a stroke, the community needs to be given knowledge about the first signs and symptoms of stroke using the FAST method based on the Health Belief Model (HBM). HBM is a theory used in health education and health promotion. Aim: can understand evidence based in the form of literature review on the effects of HBM-based health education on early signs and symptoms of stroke with the FAST method. Methods: The study was conducted by searching journals in the database "Scopus, Science Direct, and ProQuest" using predefined keywords, then the research journals were reviewed, There were five journals that met the criteria for a scientific review. The five journals then reviewed their designs, samples, treatments, and results using a critical appraisal. Result : Based on the analysis conducted, the results of the literature review state that the impact of HBM-based health education has an effect on increasing knowledge in the community. Conclusion : HBM can increase knowledge with given innovative intervention.